2010
DOI: 10.1002/art.30084
|View full text |Cite|
|
Sign up to set email alerts
|

Pattern on the antinuclear antibody–HEp‐2 test is a critical parameter for discriminating antinuclear antibody–positive healthy individuals and patients with autoimmune rheumatic diseases

Abstract: Objective. To identify features of antinuclear antibody (ANA)-HEp-2 test results that discriminate ANA-positive healthy individuals and patients with autoimmune rheumatic diseases (ARDs).Methods. We sequentially retrieved data on 918 healthy individuals and 153 patients with ARDs after clinical assessment. ANA-positive healthy individuals for whom data were available were reevaluated after 3.6-5.0 years. An ANA-HEp-2 test result was considered positive when a clear ANA pattern was observed at 1:80 dilution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
267
3
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 292 publications
(308 citation statements)
references
References 38 publications
20
267
3
18
Order By: Relevance
“…There was no association of smoking history (ever smoked, never smoked, or pack-year history) with any clinical variables (vascular, gastrointestinal, or respiratory) studied in our cohort, which reemphasizes the usefulness of appropriate statistical analysis to elucidate the association described by Hudson et al (1). However, our cumulative proportional survival analysis revealed that survival was decreased in past or present smokers (i.e., those designated as ever having smoked) compared with those who had never smoked ( Figure 1A).…”
Section: To the Editorsupporting
confidence: 51%
See 2 more Smart Citations
“…There was no association of smoking history (ever smoked, never smoked, or pack-year history) with any clinical variables (vascular, gastrointestinal, or respiratory) studied in our cohort, which reemphasizes the usefulness of appropriate statistical analysis to elucidate the association described by Hudson et al (1). However, our cumulative proportional survival analysis revealed that survival was decreased in past or present smokers (i.e., those designated as ever having smoked) compared with those who had never smoked ( Figure 1A).…”
Section: To the Editorsupporting
confidence: 51%
“…We commend Hudson and colleagues on their study demonstrating the adverse effects of smoking in scleroderma (1). They used a well-designed Comprehensive Smoking Index (2) for evaluating all vascular, gastrointestinal, and respiratory outcomes, applying simple exposure variables (e.g., ever smoking, never smoking, or pack-years of smoking) to a few clinical outcomes.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, national and international studies estimate a frequency of approximately 13% positive results and titer of 1/80 in the general population (11,17) . This scenario becomes even more problematic in view of the widespread use of this test.…”
mentioning
confidence: 99%
“…In fact, in recent years the relevance of IIF on ANA-HEp-2 interpretation has been consistently emphasized (11) . The observed pattern may provide preliminary information on the nature of the autoantibody in a given sample and even indicate which additional and specific tests should be conducted.…”
mentioning
confidence: 99%